The Role of Local IT.A.CA’ Networks in Territorial Development Processes. An Exploratory Study Starting from a Transcalar Reading - Epifani, Federica; Nocco, Sara (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2024)
IT.A.CÀ festival represents an innovation for at least two reasons: on one hand, the festival’s vision aims to boost the progressive awareness of the tourist/host, here intended as “temporary citizen”, as she/he experiences a place; on the other hand, the organization structure is based on a complex networking system made up of vertical (among national committee and local networks) and horizontal (among local stakeholders) ties. Through the analysis of reporting documents and other documentation produced by the festival organizers since 2009, as well as surveys, the research studies IT.A.CÀ’s multi-level network structure. The aim is not only to achieve a better understanding of the functioning and rooting processes, but also to clarify if and how the involvement of local stakeholders within IT.A.CÀ’s nationwide network affects the spread of a new way to conceive tourist destinations. More specifically, we suggest that local networks linked to IT.A.CÀ can be intended as a driver for social innovation at local level, whether they stem a virtuous auto-poietic process according to which synergies among network members favour new opportunities for cooperation and shared project design.